(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2018)
It is with great sorrow and sadness that we inform our readers that our esteemed colleague Artur Olímpio F. Gonçalves da Silva, who by the way sent a last article to this issue, left us. He was a formidable colleague, an investigator, a scientist, and a great human being who left his sign and friendship to those who had the privilege of knowing him. In this hour of mourning for the family, for all Arthur’s friends and from all readers, R-LEGO and the School of Economic and Organizational Sciences (ECEO) wish the most respectful condolences to the family. Until forever, Arthur!